Design of an e-Invoice System Production Information at Haruki Nihongo Gakkou Training Institute Klaten based on Open Source Enterprise Resource Planning Using Odoo Version 16 - Widyanti, Dika Vivi; Amiyati, Novi Rara; Salsabila, Salma -; Handoyo, Leonardo Saputro (Admisi dan Bisnis, 2024)
LPK Haruki Nihongo Gakkou, a Japanese-based training institute, faced challenges with inefficient business processes and a cumbersome invoicing system. This paper presents a case study on how they successfully implemented an Odoo-based Enterprise Resource Planning (ERP) system with a Point of Sales (POS) module to address these issues and create a streamlined, integrated E-Invoice system. The paper emphasizes the need for a digital solution to simplify the school's business flow and improve operational efficiency. It details the selection process for the Odoo-based ERP system, highlighting how the system was customized to meet the specific needs of LPK Haruki Nihongo Gakkou identified through interviews and instructions. The implemented system underwent rigorous testing and evaluation by the school, ensuring its effectiveness and user-friendliness. The results showcase the significant improvements achieved through the new system. The paper discusses the positive impact on operational efficiency, streamlined business processes, and simplified invoicing procedures. Additionally, it underlines the enhanced system integration, allowing for seamless data flow across various departments. This case study demonstrates the successful implementation of an Odoo-based ERP system for E-Invoicing in the educational sector. It provides valuable insights for other organizations seeking to improve their business processes and achieve greater operational efficiency through digital integration.